Impact of non-implementation of time, cost and quality management procedures in the Nigerian construction industry - Ibironke, Olajide Timothy (Penerbit UKM, 2012)
The study is an assessment of time, cost and quality management in the Nigerian construction industry, and its objective is to examine the impact of non-implementation of these factors in the Nigerian construction industry. This study is limited to the view of a convenient sample of professional i.e. Architects, Builders, Quantity Surveyors and Engineers. The method used to collect data were questionnaire and interview while the data collected were subjected to descriptive statistical analysis using percentage, mean score and frequency. The study revealed that the impact of non compliance with time,costs and quality management procedures is building collapse as evident in the Nigerian constructions industry today. Others includes high cost of construction, which make building constructions very high thus leading to project abandonment which constitute nuisance to the built environment and this can lead to lost of public confidence in the industry. The study recommends that modalities should be put in place by government and concerned professional bodies to guide against fraud, the relevant authority like SON (Standard Organization of Nigeria) should wake up from slumber and come up with standards for construction component and lastly the National Building Code should be adopted for use in the building construction in all its ramifications.